2015
DOI: 10.1038/jhh.2014.129
|View full text |Cite|
|
Sign up to set email alerts
|

Adiposity and blood pressure among 55 000 relatively lean rural adults in southwest of China

Abstract: Obesity is a strong determinant of blood pressure. Uncertainty remains, however, about which indices of adiposity most strongly predict blood pressure, particularly among those who were relatively lean, such as those from rural China. We analyzed cross-sectional data on 55 687 (38.3% men) participants aged 30–79 years who were enrolled into the China Kadoorie Biobank from a rural county in southwest of China during 2004–2008. Measured body mass index (BMI) and waist circumference (WC) were related to blood pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 33 publications
(47 reference statements)
0
14
0
1
Order By: Relevance
“…This is the most common cause of chronic liver disease in the United States and is strongly linked to metabolic risk factors, including diabetes, insulin resistance, dyslipidemia and metabolic syndrome . In this sense, subjects who have combinations of obesities during childhood and adolescence are more likely to be health outcomes during adulthood .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is the most common cause of chronic liver disease in the United States and is strongly linked to metabolic risk factors, including diabetes, insulin resistance, dyslipidemia and metabolic syndrome . In this sense, subjects who have combinations of obesities during childhood and adolescence are more likely to be health outcomes during adulthood .…”
Section: Discussionmentioning
confidence: 99%
“…This is the most common cause of chronic liver disease in the United States and is strongly linked to metabolic risk factors, including diabetes, insulin resistance, dyslipidemia and metabolic syndrome (13). In this sense, subjects who have combinations of obesities during childhood and adolescence are more likely to be health outcomes during adulthood (6,17,26). Despite the strong evidence that there are many negative consequences of obesity, the term metabolic healthy obesity (MHO) emerged in the literature in 1982 (27,28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, dietary studies conducted in the Region showed that, as the nutrition transition unfolds, the consumption of potassium-rich foods such as wholegrain unsalted cereals, fruits and vegetables is decreasing, while the consumption of total fat, refined grains and high energy, nutrient-depleted foods is on the rise (47). Increases in body weight and adiposity, which are hallmarks of the nutrition transition, may also be contributing to further increases in blood pressure in countries of the Region (48,49).…”
Section: Current Levels Of Sodium Intake In Countries Of the Eastern mentioning
confidence: 99%
“…El estudio realizado por Hernán-dez (2010), en el que se contrasta la CC con la PAD y PAS, presentó diferencias estadísticamente significativas entre los grupos de mujeres con obesidad abdominal y normales. De igual forma, en la investigación documentada por Chen (2015), la CC en las mujeres mostró fuerte y positiva asociación con la PAS. En el presente estudio, las madres de familia con obesidad abdominal exhibieron valores de tensión arterial más altos que las normales.…”
Section: Tablaunclassified